Credit scoring in SME asset-backed securities: An Italian case study - Andrea Bedin; Monica Billio; Michele Costola; Loriana Pelizzon (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
We investigate the default probability, recovery rates and loss distribution of a portfolio of securitised loans granted to Italian small and medium enterprises (SMEs). To this end, we use loan level data information provided by the European DataWarehouse platform and employ a logistic regression to estimate the company default probability. We include loan-level default probabilities and recovery rates to estimate the loss distribution of the underlying assets. We find that bank securitised loans are less risky, compared to the average bank lending to small and medium enterprises.
urn:nbn:de:hebis:30:3-511488
Keywords: 330; credit scoring; probability of default; small and medium enterprises; asset-backed securities